THE QUALITY OF WORK LIFE IN MIGRANT WORKERS IN THAILAND: A CASE STUDY OF SRI-KHEMA MARKET, BANGSUE DISTRICT, BANGKOK - Takhiansok, Tararat; Sawangwong, Boonwat (PEOPLE: International Journal of Social Sciences, 2020)
The objective of this study 1) study the level of quality of work-life in migrant workers 2) compare the level of quality of work-life in migrant workers differentiated by personal factors. The research uses a quantitative method to study 232 participants in Sri-khema Market in Bangsue district of Bangkok. It used surveys for data collection. Statistical analysis was done using frequency, percentage, mean, standard deviation, t-test, and one-way ANOVA. If the overall ANOVA resulted in a P value less than 0.05, the Least Significant Method would be used to produce a pairwise comparison. The result found; 1. The level of quality of life overall is at a high level with a mean of 3.60. Once studied by aspect, it was found that ‘work benefiting the society’ was rated the highest at 4.17, followed by ‘fair wages’ at 4.16 and ‘safe and healthy working condition’ at 4.09 consecutively. 2. The comparison of the level of quality of life in migrant workers in Sri-khema differentiated by personal factors found: gender, marital status, education level, and income level do not induce a different level of quality of life whereas age, nationality and length of employment induce differences in the levels of quality of life.